Future-oriented implications of the resilience theory for Iran’s public libraries - َAli Zackery; Mohsen Taheri Demneh; Elahe Ebrahimi Dorcheh (تحقیقات اطلاع‌رسانی و کتابخانه‌های عمومی, 2022)
Purpose: Public libraries are faced with technological changes and unknown issues that can change their identity and mission in charting the future path for their role in social developments. In line with the use of new approaches to redefine the mission of libraries, the present research intends to provide a vision for Iran’s public libraries by using the implications of resilience theory. Method: This research was designed and implemented in the form of a three-step process: 1. studying the implications of the characteristics of a resilient system, 2. Environmental scanning through literature review by searching for research and review articles, books and reports in English language related to the subject indexed in Scopus and Google Scholar databases without applying time limits, and 3. prospecting. Findings: A resilient library has the characteristics of diversity, changeability, modularity, acceptance of slow variables, intensive feedback, social capital, innovation, ecosystem services, redundancy and publics. Among the general examples of using these features in public libraries are: using technologies at different levels and updating resources and services and library space; intellectual and skill preparation of librarians and continuous monitoring of previous experience and knowledge and current conditions; dividing the library into different departments and its federal administration; Pathology in libraries and continuous identification and follow-up of changes, though small, in various dimensions of human, environment and technology; Follow-up by managers of the conditions of each department and continuous follow-up and analysis of users’ opinions in order to satisfy them; Providing a communication platform and providing social information services in order to strengthen social capital, social cohesion, and social justice; Innovation in the thinking and action of librarians and their decisions and services; and identifying and introducing the highlights of the library to attract more audience. The future library is a phygital platform and a built space for shared co-creation. Resilient library as an experience center is a point of access for citizens to emerging technologies and a platform for popularizing science and practicing civil epistemology. The future library has a modular management structure and is a place for learning, re-learning and more importantly going beyond previous learning. Originality/value: Resilience theory has been developed to describe and address the inherent uncertainty and insecurity of major changes of systems, acknowledging that we live in a state of constant change and that there is no point in the future where we can expect everything to be static and optimal. take Therefore, libraries should not focus their energy on creating ways to continue the usual and traditional services in the future, but should look for ways to adapt intelligently to changes. The current research can be a good guide in this field for public libraries.